LEGAL PROTECTION FOR DOCTORS IN INDEPENDENT DOCTOR PRACTICE CLINIC PROVIDER OF PUBLIC SERVICES - Taufan Nugroho; Thamrin S; Abd Thalib (International Conference On Law And Social Sciences, 2024)
Doctors who work in accordance with medical “service standards and standard” operational procedures have the right to legal protection. The aim of the research is to ascertain the legal safeguards for doctors who provide general services in independent doctor practices. This kind of study employs an analytical descriptive method with secondary data and data processed through qualitative analysis, as well as a normative juridical approach. In conclusion: “As regulated in Law of the Republic of Indonesia” Number 29 of 2004 concerning Medical Practice, “Law Number 36 of 2009 concerning Health, and Regulation of the Minister of Health of the Republic of Indonesia Number” 512 of 2007 concerning Licensing and Implementation of Medical Practice, doctors are protected by law “in provide health services. Meanwhile, doctors who work in hospitals are protected by the rules contained in Article 46 of Law of the Republic of Indonesia Number 44 of 2009 concerning Hospitals.” However, in its implementation, many doctors who work in hospitals or independent practices feel wronged because the law seems to have no power at all.